2021
DOI: 10.4239/wjd.v12.i2.149
|View full text |Cite
|
Sign up to set email alerts
|

Use of glycated albumin for the identification of diabetes in subjects from northeast China

Abstract: BACKGROUND Metabolic memory is important for the diagnosis and treatment of diabetes in the early stage, and in maintaining blood glucose concentrations within the normal range. The clinical diagnosis of diabetes mellitus is currently made using fasting plasma glucose, 2 h-plasma glucose (2h-PG) during a 75 g oral glucose tolerance test, and hemoglobin A1c (HbA1c) level. However, the fasting plasma glucose test requires fasting, which is a barrier to screening, and reproducibility of the 2h-PG lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…chronic renal failure, recent transfusion, pregnancy), and/or to monitor short-term glycemic fluctuations in patients with poor metabolic control (American Diabetes Association, 2021; Giglio et al, 2020). Indeed, GA reflects mean glycemia over approximately 2-3 weeks and, compared with glycated hemoglobin by more rapid and greater changes, not influenced by red blood cell lifespan (Li et al, 2021). Interestingly, Chen et al (2017) demonstrated that, in diabetic patients on hemodialysis, high GA measurements are significantly associated with increased mortality, in contrast to an inconsistent association between higher glycated hemoglobin values and mortality risk, thus highlighting the need to monitor and optimize glycemic levels especially in the patient population with disorders affecting erythrocyte life span.…”
Section: Glycation and Advanced Glycation End-products (Ages)mentioning
confidence: 99%
“…chronic renal failure, recent transfusion, pregnancy), and/or to monitor short-term glycemic fluctuations in patients with poor metabolic control (American Diabetes Association, 2021; Giglio et al, 2020). Indeed, GA reflects mean glycemia over approximately 2-3 weeks and, compared with glycated hemoglobin by more rapid and greater changes, not influenced by red blood cell lifespan (Li et al, 2021). Interestingly, Chen et al (2017) demonstrated that, in diabetic patients on hemodialysis, high GA measurements are significantly associated with increased mortality, in contrast to an inconsistent association between higher glycated hemoglobin values and mortality risk, thus highlighting the need to monitor and optimize glycemic levels especially in the patient population with disorders affecting erythrocyte life span.…”
Section: Glycation and Advanced Glycation End-products (Ages)mentioning
confidence: 99%
“…GLY-HSA is now considered a clinical biomarker of glycemic control, even if its use is restricted to those clinical conditions in which the levels of glycated hemoglobin (HbA1c) do not reflect glycemic status (i.e., pregnancy, chronic renal failure, or transfusion), or to the evaluation of short-term glycemic fluctuations in patients with poor metabolic control. Indeed, GLY-HSA reflects mean glycemia over approximately 2–3 weeks and, compared with HbA1c is not influenced by red blood cell lifespan [ 20 ]. However, as stated by the International and National Recommendations, it cannot be used yet for the diagnosis of diabetes [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%